European real-world data about the use of a new delivery system containing a preservative-free multi-dose glaucoma treatment. Issue 3 (May 2021) - Denis, Philippe; Duch, Susana; Chen, Enping; Klyve, Per; Skov, Jesper; Puska, Païvi; Erb, Carl
Background: Glaucoma treatments are mostly presented in uni-dose or multi-dose format. A certain number of patients with visual acuity and dexterity problems may have problems in instilling eye drops. Aim: To assess patient satisfaction and ease of use of a preservative-free glaucoma treatment (dorzolamide/timolol) in a new and innovative patented multi-dose delivery system. Methods: Retrospective, international, multicentre, non-interventional study in 788 adult patients using a multi-dose delivery system for at least 28 days. Results: Mean patient age was 68.1 ± 12.1 years. Mean duration of multi-dose delivery system use was 132.1 ± 125.1 days; 66.5% of the patients previously used multi-dose and 33.5% uni-dose delivery systems (n = 734); 78.3% of the patients were satisfied or very satisfied with the multi-dose delivery system. A significant majority (all p ≤ 0.045) of patients with a QuickDash® score between [0 to 25[ (66.4%, n = 211) and [50 to 75[ (81.8%, n = 11) rated multi-dose delivery system as easy or very easy to open and significantly more subjects in the [0 to 25[ (72%) score group rated multi-dose delivery system as being better or much better than their previous device (n = 211). Significantly (all p < 0.01) more subjects with available visual acuity results rated multi-dose delivery system as good, better or much better than their previous dispensing device. Conclusion: The tested multi-dose delivery system was highly accepted. It is, therefore, suitable for glaucoma patients with decreased visual acuity and/or dexterity problems. Further studies may be necessary to assess the easiness of use of this easy-to-grip delivery system.